M.U.S.T. handbook 1998. (Styles and Classics Philippines, 1997)
MUST stands for Motorist Utilities and Services Tool. It provides information on everything a motorist in the Philippines needs to know, from getting a license to keeping a maintenance record log. It also includes a travel guide on the best resorts, golf courses, dive sites, Philippine festivals, directory of foreign embassies and consulates, and maps of the CALABARZON area, North Luzon, Baguio, Cebu, and Davao. Another helpful feature is the maps and street index to a mini-gazetteer of Metro Manila and nearby areas. The last section is the business directory, which is a listing of consumer establishments and services in and around Metro Manila. Maps are colored and contain legends for gasoline stations, drug stores, 24-hour stores and restaurants, and banks. This is a really convenient tool, on and off the road.